Transforming knowledge - Minnich, Elizabeth Kamarck (Temple University Press, 2005)
This is a book about how we define knowledge and how we think about moral and political questions. It argues that the prevailing systems of knowledge, morality, and politics are rooted in views that are exclusionary and therefore legitimate injustice, patriarchy, and violence. That is, these views divide humans into different kinds along a hierarchy whose elite still defines the systems that shape our lives and misshape our thinking. Like the first edition of Transforming Knowledge, this substantially revised edition calls upon us to continue to liberate our minds and the systems.